Globalisation and teacher education in the BRICS countries : the positioning of research and practice in comparative perspective - Menter, Ian, 1949-; Valeeva, Roza, 1954-; Prata-Linhares, Martha, 1959- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This edited volume critically engages with the debate on teacher education systems in the BRICS countries (Brazil, Russia, India, China, and South Africa), considering the effects of contemporary globalisation processes on each differing geographic location. Written by leading researchers from the BRICS countries, chapters reveal the processes present in these countries regarding the often-problematic relationships between research, policy and practice, as well as the extent of integration between higher education institutions and basic schools, with particular emphasis on teachers' professional development. With a particular focus on the role of research and positioning of the school practicum, the book offers new insights into the processes of educational globalisation. It presents comparative discussions of the development of BRICS and the significance of education and preparation of teachers between the five nations, each with differing educational traditions. Ultimately, this book provides a unique picture of teacher education systems across these five countries and offers new perspectives that will enrich the work of scholars, students, and researchers in the fields of international and comparative education, education policy and politics, globalisation and teacher education. Policy makers and teacher educators involved in globalisation studies may also benefit from the volume more broadly"--
Part 1: Setting the scene -- The BRICS alliance and the impact of globalisation on teacher education worldwide / Ian Menter -- The BRICS countries in the educational universe / Roza Valeeva and Martha Prata-Linhares -- Part 2: The five cases -- Trends in teacher education in Brazil: where are we going to? / Martha Prata-Linhares, Helena Amaral da Fontoura and Maria Alzira de Almeida Pimenta -- Linking theory and practice in training teachers: a Russian perspective / Roza Valeeva, Aydar Kalimullin, Tatiana Baklashova and Liliia Latypova -- Changing norms of policies and practices for teacher education in India: implications and concerns -- Balwant Singh and Manpreet Kaur -- Towards practice-based teacher education in China: policies and practices / Congman Rao -- Inquiry-focused and practice-based teacher education in partnership with schools: a South African perspective / Sarah Gravett, Sarita Ramsaroop and Nadine Petersen -- Part 3: Comparative analysis -- The impact of globalization on teacher education in the BRICS countries / Ian Menter, Roza Valeeva and Martha Prata-Linhares -- Afterword. The BRICS countries present and future: glocalization, culture and fragmented transformation / Maria Teresa Tatto.
Keywords: Education and globalization -- Brazil; Education and globalization -- Russia (Federation); Education and globalization -- India; Education and globalization -- China; Education and globalization -- South Africa; Teachers -- Training of -- Brazil; Teachers -- Training of -- Russia (Federation); Teachers -- Training of -- India; Teachers -- Training of -- China; Teachers -- Training of -- South Africa; EDUCATION / General; EDUCATION / Comparative